2014
DOI: 10.3810/psm.2014.09.2075
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Musculoskeletal Ultrasound to Assess and Quantify Muscle Glycogen Content. A Novel Approach

Abstract: These results demonstrate that skeletal muscle glycogen can be measured quickly and noninvasively through high-frequency ultrasound using MuscleSound technology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
96
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(101 citation statements)
references
References 38 publications
2
96
1
2
Order By: Relevance
“…For example, Pillen et al (2009) demonstrated that increases in interstitial fibrous and fat tissues were associated ( r = 0.87) with increases in echo intensity. Hill and Millan (2014) and Nieman et al (2015) showed that changes in rectus femoris and vastus lateralis echo intensity are strongly related ( r = 0.88–0.92) to changes in skeletal muscle glycogen content following cycling exercise. Although, several previous studies have demonstrated decreases in echo intensity following chronic resistance training (Pinto et al, 2014; Radaelli et al, 2014), Radaelli et al (2014) suggested that the mechanism for changes in echo intensity is unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Pillen et al (2009) demonstrated that increases in interstitial fibrous and fat tissues were associated ( r = 0.87) with increases in echo intensity. Hill and Millan (2014) and Nieman et al (2015) showed that changes in rectus femoris and vastus lateralis echo intensity are strongly related ( r = 0.88–0.92) to changes in skeletal muscle glycogen content following cycling exercise. Although, several previous studies have demonstrated decreases in echo intensity following chronic resistance training (Pinto et al, 2014; Radaelli et al, 2014), Radaelli et al (2014) suggested that the mechanism for changes in echo intensity is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound echo intensity has also been used as a surrogate of muscle quality (Pillen et al, 2009; Arts et al, 2012; Fukumoto et al, 2012; Radaelli et al, 2013) and as an indicator of skeletal muscle glycogen content and tissue hydration (Sarvazyan et al, 2005; Hill and Millan, 2014; Nieman et al, 2015). For example, Pillen et al (2009) demonstrated that increases in interstitial fibrous and fat tissues were associated ( r = 0.87) with increases in echo intensity.…”
Section: Discussionmentioning
confidence: 99%
“…New cutting edge ultrasound technology [45] is being utilized routinely by the world's most elite professional athletes (i.e. Tour de France) to directly measure muscle glycogen in a few minutes at the bedside[45].…”
Section: Metabolic Response To Icu- Relationship To Exercise Stress Amentioning
confidence: 99%
“…Tour de France) to directly measure muscle glycogen in a few minutes at the bedside[45]. This technology is utilized by athletes to predict and prevent overtraining and guide nutritional needs during training.…”
Section: Metabolic Response To Icu- Relationship To Exercise Stress Amentioning
confidence: 99%
“…It employs a portable device and cloud-based software. In a study funded by MuscleSound and led by the founder of the company, elite cyclists had muscle glycogen assessed before and after an intense bout of ergometer cycling [ 44 ]. The ultrasound value of muscle glycogen change compared favorably to that obtained with muscle biopsies ( r = 0.81).…”
Section: Misdirected: Indirect and Direct Measuresmentioning
confidence: 99%